Ash as an effective additive in the manufacture of concrete and reinforced concrete structures and products - Abdushkurov, Farit; Atambayeva, Dana; Assan, Azat; Beisenov, Talgat (Рroblems of engineering and professional education, 2023)
In the new reality the actual problem is the availability of additives in concrete. The effectiveness increase of the reinforced concrete structures through the use of lightweight concrete of new effective local materials is one of the factors in the development of infrastructure construction. Reduction of material consumption and complexity of their prefabrication, transport costs and construction time of buildings is ensured by the resulting weight of the structures.